2019
DOI: 10.1097/ftd.0000000000000665
|View full text |Cite
|
Sign up to set email alerts
|

Linezolid Dosing in Patients With Liver Cirrhosis: Standard Dosing Risk Toxicity

Abstract: Background: Limited data regarding altered linezolid pharmacokinetics in patients with liver cirrhosis are available. The objective of this study was to evaluate the pharmacokinetics, efficacy and safety of linezolid in cirrhotic patients. Methods: A case–control 1:1 study of patients undergoing linezolid therapeutic drug monitoring was conducted between January 2015 and June 2017. Cases with liver cirrhosis were matched with controls by age, body weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…The study also showed that liver cirrhosis was an independent risk factor for thrombocytopenia. Luque et al (22) investigated the relationship between linezolid standard dose and risky toxicity in patients with liver cirrhosis and found that patients were more likely to achieve supratherapeutic concentrations and to suffer severe thrombocytopenia. The reason may be a reduced nonrenal clearance (26,27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study also showed that liver cirrhosis was an independent risk factor for thrombocytopenia. Luque et al (22) investigated the relationship between linezolid standard dose and risky toxicity in patients with liver cirrhosis and found that patients were more likely to achieve supratherapeutic concentrations and to suffer severe thrombocytopenia. The reason may be a reduced nonrenal clearance (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the findings of a previous PPK/PD study of Japanese patients (21), which included 4 patients with severe cirrhosis. Another study (22) about the risk of standard dose of linezolid for patients with liver cirrhosis suggested that a reduced dose at 600 mg/24 h was preferred. What is more, 400 mg, q24 h was sufficient to achieve the target (AUC 0 -24 /MIC Ն80) (probability, 97.9%) against pathogens with an MIC of 2 g/ml for patients with LD with a PTA of Յ20%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review specifically highlighted the lack of recommendations for linezolid dose adjustment in renal impairment despite the elevated myelosuppression risk. Luque et al (17) demonstrated that standard doses of linezolid in patients with moderate to severe cirrhosis resulted in concentrations of Ͼ8 mg/liter, with thrombocytopenia observed in 41.7% to 66.7% of patients. Our previously described assay methodology therefore provides research groups with an opportunity to profile linezolid and metabolite concentrations and better characterize this cumulative risk potential in specific populations.…”
mentioning
confidence: 99%
“…These are likely due to the early intervention via initial dose reduction to avoid linezolid overexposure, as patient demographics, baseline laboratory values, microorganisms, and the type of infection were not significantly different between the two groups. Other factors affecting the pharmacokinetics of linezolid include drug–drug interaction [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], liver dysfunction [ 25 , 26 ], and critical illness with/without acute kidney injury [ 27 , 28 ]. In our study, there were no episodes of linezolid co-administration with rifampicin, omeprazole, amlodipine, amiodarone, or dexamethasone, and there were no differences in the population of patients co-administered with levothyroxine in both groups, indicative of a limited effect of drug–drug interactions.…”
Section: Discussionmentioning
confidence: 99%